Taʾthīr taṭbīq al-wasīlah al-taʿlīmiyyah "Live Worksheet" ʿalā mahārat al-kitābah li-ṭālibāt al-ṣaff al-tāsiʿ: dirāsah kammiyyah fī al-madrasah al-mutawassiṭah al-islāmiyyah al-ahliyyah "al-Muʿallimāt" Cukir, Jombang, Jāwī al-Sharqiyyah - Roisatul Muâ€™awwanah; Fathur Rohman (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2022)
This article examines the effect of using Liveworksheet-based online learning media in improving the writing skills of ninth graders at Madrasah Tsanawiyah Mu'allimat Cukir, Jombang. This research aims to; (1) Know the application of Live Worksheet Online LKS in Grade Nine language programs Madrasah Tsanawiyah Cukir, Jombang; (2) Knowing the learning of writing skills of the ninth grade students of the language program; (3) Knowing the effect of applying the LKS Online Liveworksheet on the writing skills of the ninth graders of the language program. The method used is quantitative with tests, interviews and questionnaires, then analyzed using the Man Whitney Test. The results of the research: (1) The use of LKS Online Liveworksheet learning media in the ninth grade of the madrasah tsanawiyah mu'allimat language program can support students to be more interested in learning Arabic, with a more attractive LKS display with various pictures and videos. (2) Arabic language learning, especially writing skills in the ninth grade of the language program, is carried out using two methods, namely: lecture method and question and answer method. Occasionally also use the method insya'. (3) Liveworksheet-based online worksheets are effective for improving writing skills. This is indicated by the test results from the man withney test with a Sig value of 0.000 < 0.005.